Identification of molecular markers in GDF9gene of Egyptian goat breeds - Metawi H.; Rashed M.; Anous M.; Khattab A.; Abd El Halim H.; Mohamed L. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The aim of this study was to investigate the presence of polymorphism in growth differentiation factor 9 (GDF9) genes and their possible association with litter size in two more prolific goat breeds in Egypt.The does were selected according to their litter size trait, using the pedigree records. Each doe was assembled into two groups: single birth (SB, n = 30) and multiple births (MB, n = 30). In Baladi goat breed, polymorphic restriction pattern indicate presence of one band with 710 bp among all SB does and three bands with 710 and 600 bp and 100 bp for MB does In Zaraibi goats, polymorphic restriction pattern indicate presence of one band with 700bp among all SB does and two bands with 600 bp and 100 bp for MB does. These result showed that presence of polymorphic of GDF9 in Baladi goat and monoomorphic of GDF9 in Zaraibi MB does. The mutations in the GDF9 gene associate with fecundity were identified only in investigated MB Egyptian goat breeds. Alignment of the tested alleles with copracircus GDF9 sequence from gene bank showed transition in multiple births does from CCGAGG to GTTCAT and from TT to AG in regions from 52 to 57 and from 61 to 62, respectively.The study indicates the possibilities of using these markers for selection for high prolificacy in Egyptian goats.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)